In the usual sense, it has no inverse function. Since it is not an injection (f(0)=f(2)=0), an inverse function would have to map 0 both to 0 and 2, and that’s impossible.
However, if you restrict the domain to [1,+oo> (to make it injective), and the codomain to [-1,+oo> (to make it surjective), then it has an inverse function, given by g(y)=1+sqrt(y+1).
Given:
The given expression is:
To find:
Part A: The expression by factoring out the greatest common factor.
Part B: Factor the entire expression completely.
Solution:
Part A:
We have,
Taking out the highest common factor 3y, we get
Therefore, the required expression is .
Part B:
From part A, we have,
By grouping method, we get
Therefore, the required factored form of the given expression is .
Answer:
X=3
Step-by-step explanation:
2(4x−3)−8=4+2x
2)(4x)+(2)(−3)+−8=4+2x
8x+−6+−8=4+2x
8x−14=2x+4
8x−14−2x=2x+4−2x
6x−14=4
6x−14+14=4+14
6x=18
x=3
Answer:35
Step-by-step explanation: